Displaced lower third molar tooth into the submandibular space: Two case reports - Kose, Ibrahim (Medknow Publications & Media Pvt Ltd, 2014)
The aim of this article is to emphasize that the accidental displacement of a lower third molar during extraction is a rare, but potentially serious complication. We present two case reports on a lower third molar tooth dislodged into the submandibular space following its removal from the sockets and the subsequent management of this rare complication. Differences in the direction of displacement, the size of fragment, delay in retrieval, and tissue reactions can all influence this potential serious complication and hence no one technique is uniformly applicable. Though a rare complication, clinicians must be aware of possible lower third molars dislodgement into tissue spaces and the necessity to initiate prompt and appropriate management.